Life Satisfaction and Insomnia among Elderly Community Dwellers of Lalitpur, Nepal - Khagi, Bina R; Timalsina, Rekha; Chhantyal, Anita; Shiwakoti, Shrijana; Maharjan, Manju (Journal of Institute of Medicine Nepal, 2019)
Introduction: Life satisfaction during elderly is essential in ageing process. Globally, insomnia is a problem that degrades the health of elderly people, which also interferes with the quality of life. Methods: A descriptive cross-sectional study was conducted to identify life satisfaction and insomnia among 501 community dwellers elderly of Lalitpur by using structured interview schedule on socio-demographic information, Satisfaction with Life Scale (SWLS) to measure a life satisfaction and Pittsburgh Insomnia Rating Scale (PIRS) to identify the prevalence of insomnia. Results: Data was edited, classified, and coded manually. Then, data entry and data cleaning were done using Epi data software and data analysis was done using SPSS software version 16. Descriptive and inferential statistics were used to analyze data. The study showed that 31.9% and 35.7% of respondents were highly satisfied and satisfied with their life respectively. However, 6% and 0.6% of respondents were dissatisfied and extremely dissatisfied with their life respectively. Study reveals that 50.5% of respondents had insomnia. Ethnicity, current job status, and health problems during night sleep were significantly associated with life satisfaction. Similarly, age, marital status, educational status, current job status, current physical health problems, presence of disease, taking medication at present and health problems during night sleep were significantly associated with insomnia. Conclusion: Most elderly people were satisfied with their life, but majority of them suffered from insomnia. Therefore, it is necessary to plan awareness program regarding life satisfaction and insomnia by concerned authority to help elderly to stay healthy and improve their quality of life.